A systems-level understanding of adversarial behaviour. (1st January 2012) - Weiss, Lora G.; Briscoe, Erica; Whitaker, Elizabeth; Trewhitt, Ethan; Hayes, Heather; Horgan, John
Modelling behaviour related to the perpetration of improvised explosive devices is extremely complex. Behavioural aspects range from those who create a plan to those who gather supplies for developing the devices to those who passively look the other way. Developing computational approaches to understanding such behaviour necessitates either a decomposition of behavioural activity into smaller, manageable behaviours or generalising larger, group behaviour where gross trends are observed. This may suffice for particular applications; however, additional consideration can be given to developing more comprehensive approaches. Specifically, for those seeking to understand terrorism, a number of social, cultural and behavioural perspectives are being developed by experts worldwide. These perspectives may complement each other or they may be in conflict, but they equally contribute to a broader understanding. Our research is developing computational methods to analyse and experiment with differing views and perspectives of potential influences on adversarial behaviour at this system-level.